2019
DOI: 10.1017/jfm.2019.696
|View full text |Cite
|
Sign up to set email alerts
|

Gelatine cavity dynamics of high-speed sphere impact

Abstract: We investigate the impact and penetration of a solid sphere passing through gelatine at various impact speeds up to 143.2 m s −1 . Tests were performed with several concentrations of gelatine. Impacts for low elastic Froude number Fr e , a ratio between inertia and gelatine elasticity, resulted in rebound. Higher Fr e values resulted in penetration, forming cavities with prominent surface textures. The overall shape of the cavities resembles those observed in water-entry experiments, yet they appear in a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…However, as De increases, i.e., when the viscoelastic timescales become increasingly comparable to the capillary time, the jet needs larger speeds to traverse the droplet. This is in line with previous experiments where by increasing the elastic modulus of gelatin the cavity depth of an impacting sphere would decrease, keeping the impact velocity constant 35 . These results show that viscoelastic properties as described by De significantly change the traversing dynamics.…”
Section: Critical Velocity For Traversingsupporting
confidence: 92%
See 1 more Smart Citation
“…However, as De increases, i.e., when the viscoelastic timescales become increasingly comparable to the capillary time, the jet needs larger speeds to traverse the droplet. This is in line with previous experiments where by increasing the elastic modulus of gelatin the cavity depth of an impacting sphere would decrease, keeping the impact velocity constant 35 . These results show that viscoelastic properties as described by De significantly change the traversing dynamics.…”
Section: Critical Velocity For Traversingsupporting
confidence: 92%
“…This is in line with previous experiments where by increasing the elastic modulus of gelatin the cavity depth of an impacting sphere would decrease, keeping the impact velocity constant. 35 These results show that viscoelastic properties as described by De significantly change the traversing dynamics. This is crucial information when trying to understand needle-free injections on skin, as it has been shown that skin has viscoelastic properties.…”
Section: Resultsmentioning
confidence: 70%
“…Within the reported cavity types our observations can be best compared to the shallow seal regime, which we found for G = 3.5 kPa and W e jet > 3500, F r e > 1200; G = 0.8 kPa and W e jet > 650, F r e > 1000; G = 0.2 kPa and W e jet = 125-215, F r e > 700-1300. Our results are in agreement with Kiyama et al, where they found shallow seals starting from F r e 200 -400 and transitioning to surface seal at F r e > 10 4 [67]. We did not observe a transition to a surface seal as for our experiments F r e < 10 4 .…”
Section: Regime 5: Splash and Injectionsupporting
confidence: 93%
“…We can compare our results by looking at studies where high-speed projectiles were impacted on various concentrations of gelatin gels, and cavity regimes were defined based on projectile elastic Froude number (F r) as function of substrate G [67]. Within the reported cavity types our observations can be best compared to the shallow seal regime, which we found for G = 3.5 kPa and W e jet > 3500, F r e > 1200; G = 0.8 kPa and W e jet > 650, F r e > 1000; G = 0.2 kPa and W e jet = 125-215, F r e > 700-1300.…”
Section: Regime 5: Splash and Injectionmentioning
confidence: 99%
“…a few tens of microns below the surface). Similar to the fluid mechanics created by an object impacting on a free surface (Kiyama et al 2019), laser focusing gives origin to an explosive expansion of a cavity front into the liquid and a recoil induced material expulsion (or splash) into the air (Vogel & Venugopalan 2003;Apitz & Vogel 2005;Thoroddsen et al 2009). While typical impact velocities of objects result in cavity front velocities of tens of metres per second, and splashes rising in opposite direction with similar velocities, laser induced splashes are considerably faster.…”
Section: Introductionmentioning
confidence: 97%